2021
DOI: 10.1186/s12884-021-03717-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of exercise during pregnancy on racial/ethnic health disparities and birth outcomes

Abstract: Background Non-Hispanic black (NHB) pregnant women disproportionately experience adverse birth outcomes compared to Non-Hispanic white (NHW) pregnant women. The positive effects of prenatal exercise on maternal and neonatal health may mitigate these disparities. This study evaluated the influence of prenatal exercise on racial/ethnic disparities in gestational age (GA), birthweight (BW), and risks of preterm birth (PTB), cesarean section (CS), and low-birthweight (LBW) neonates. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…In addition, higher weight and lower length in BIPOC offspring increased weight: length ratio. However, in agreement with previous findings, exercise during appears to mitigate interracial disparities in birth outcomes (Raper et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In addition, higher weight and lower length in BIPOC offspring increased weight: length ratio. However, in agreement with previous findings, exercise during appears to mitigate interracial disparities in birth outcomes (Raper et al, 2021).…”
Section: Discussionsupporting
confidence: 92%
“…These findings coupled with multiple significant correlations with other markers of morphometrics, as well as placental volume and efficiency confirm that increasing exercise intensity benefits pregnancy and fetal growth (Bø et al, 2016;Siebel et al, 2012;Yu et al, 2022). This information aligns with a systematic review and meta-analysis (Perales et al, 2016;Raper et al, 2021) which showed that vigorous intensity maternal exercise significantly increases gestational length and reduces risk of prematurity (Beetham et al, 2019).…”
Section: Prenatal Exercise Intensitysupporting
confidence: 79%
“…There were a total of 61 studies that were incorporated in this analysis [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 ,…”
Section: Resultsmentioning
confidence: 99%
“…This analysis comprised a total of 16 studies [ 27 , 31 , 33 , 40 , 41 , 42 , 48 , 52 , 57 , 66 , 69 , 72 , 73 , 75 , 76 , 83 ]. There was no statistically significant association (z = 1.25; p = 0.21) between physical activity during pregnancy and the likelihood of low birth weight (RR = 0.84, 95% CI = 0.65, 1.10, I 2 = 9%, P heterogeneity = 0.35).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation